Evaluating nursing competence with the Nurse Competence Scale from an ontological and contextual point of view: An integrative literature review - Lejonqvist Gun-Britt; Kajander-Unkuri Satu (SAGE Journals, 2022)
Evaluating nursing competence is challenging and among many instruments the Nurse Competence Scale is one of the most used. This integrated literature review aimed to explore how ontological and contextual nursing competence becomes evident in evaluations done with it and the value of using it for professional development in nursing.
The starting point was a former systematic review and additional searches were done using electronic databases with key words and Boolean operators. The search followed the PRISMA search strategy and the articles were appraised by JBI Critical Appraisal Checklist. 34 original research articles between January 2004–April 2020 were included. The data were displayed and analysed descriptively. Results showed that the Nurse Competence Scale covers both ontological and contextual competence, that the competence profiles vary in different cultures, cohorts and contexts, but that it is suitable for evaluating and following up competence development in nursing.